Size control of carbon-supported platinum nanoparticles made using polyol method for low temperature fuel cells - Favilla, Pablo Cesar (2013)
The aim of this work is to present the results of the synthesis of Pt nanoparticles using the modified polyol method, using carbon black powder Vulcan XC-72R as a support. Two different techniques were used to synthesize the catalysts: (a) fixing the initial concentration of the precursor (2 mM in H2PtCl6) while adding the required amount of support to obtain different nominal loads of platinum; (b) changing the initial concentration of the precursor to obtain altogether 10 wt% nominal load of platinum. Catalysts were characterized using X-ray diffraction, transmission electron microscopy and cyclic voltammetry. The particles obtained ranged in sizes between 2.2 and 6.2 nm. These sizes were controlled by the initial concentration of the precursor. It has been found that the concentration of nanoparticles formed during synthesis was the same regardless of (a) the initial concentration of the precursor and (b) the amount of carbon support. In order to explain experimental results a new and simple statistical and geometrical treatment is used.